Methodology matters: comparing sample types and data collection methods in a juror decision-making study on the influence of defendant race - Maeder, Evelyn M. (Psychology, crime & law, 2018)
Researchers have expressed concerns that using online and/or student samples in juror decision-making studies significantly diminishes the trustworthiness of results. The purpose of this study was to test whether these samples might yield different demographics, attentiveness to a trial stimulus, and verdict decisions. Participants read a fabricated robbery trial transcript - in which we manipulated the defendant’s race (White, Black, Aboriginal Canadian) - then made verdict decisions and completed manipulation checks. We tested four Canadian samples: non-student community members online, non-student community members in-lab, students online, and students in-lab. Addressing one of the common criticisms of online samples, those who participated online were no more likely to fail manipulation checks than those who completed the study in-lab. We also found an interaction among data collection method, defendant race, and verdict - participants who completed the study online were more lenient towards White defendants, suggesting that the presence of a research assistant (and/or other participants) in the room while participants completed the study affected the expression of racial bias. Our findings allay some common concerns about online and student samples, but also show some limitations, including clear demographic differences.